Editorial: Globalization, Human Security and The Value of Education - Mahayasa, Dias Pabyantara Swandita; Utami, Arum Tri (JUSS (Jurnal Sosial Soedirman), 2023)
Editorial: Globalization, Human Security and The Value of Education